A divina loucura de Antônio Conselheiro: encontro, tragédia e redenção. - Lígia Burton Ferreira (2021)
The goal of this research was to analyze the socially and historically established identity of Antônio Conselheiro, leader in the Canudos war, from fragments present in different existing narratives and the consequences of the diagnosis of psychosis established by the doctor Nina Rodrigues. As an epistemological basis, the studies of Critical Theory of Society are used, especially the notion of fragments by Walter Benjamin, in order to form a constellation about the identity of this subject stigmatized as crazy, mystical and fanatic. Based on the collection of fragments left at the margins of history, it is proposed to see the death of Antônio Conselheiro as an opening, the origin, for another possible understanding of history. In this sense, the collected articles are not exposed to an external logic, but presented in their uniqueness and singularities. When pausing to study the phenomenon, an attempt is made to restore the object to its unique and irreducible dimension, since by joining the pieces of its history, the hope of a fair political horizon is glimpsed. Our intention is not to write a verdict on his identity or even on the events of the war, rather, we seek to find significant fragments of these events, including imagery, that allow some gaps, which still exist, about this individual to be filled, establishing new ones meanings, which sometimes illuminate nuances little explored so far, both in the literature and in other ways of approaching it.